The Cervical Cancer Treatment Gap in Mexico Under Seguro Popular, 2006-2016 - Sean P. McClellan; Karla Unger-Saldaña; Priscilla Espinosa-Tamez; Erick Suazo-Zepeda; Michael B. Potter; Salim Abraham Barquet-Muñoz; Leticia Torres-Ibarra; Hector Lamadrid-Figueroa; Martín Lajous (Taylor & Francis Group, 2023)
ABSTRACTFrom 2005 to 2019, the Mexican government financed cervical cancer treatment for individuals without social security insurance through Seguro Popular's Fund for Protection against Catastrophic Health Expenses. To better understand the impact of this program on access to treatment, we estimated the cervical cancer treatment gap (the proportion of patients with cervical cancer in this population who did not receive treatment). To calculate the expected number of incident cervical cancer cases we used national surveys with information on insurance affiliation and incidence estimates from the Global Burden of Disease study. We used a national claims database to determine the number of cases whose treatment was financed by Seguro Popular. From 2006 to 2016, the national cervical cancer treatment gap changed from 0.61 (95% CI 0.59 to 0.62) to 0.45 (95% CI 0.43 to 0.48), with an average yearly reduction of −0.012 (95% CI −0.024 to −0.001). The gap was greater in states with higher levels of marginalization and in the youngest and oldest age groups. Although the cervical cancer treatment gap among individuals eligible for Seguro Popular decreased after the introduction of public financing for treatment, it remained high. Seguro Popular was eliminated in 2019; however, individuals without social security have continued to receive cancer care financed by the government in the same healthcare facilities. These results suggest that barriers to care persisted after the introduction of public financing for treatment. These barriers must be reduced to improve cervical cancer care in Mexico, particularly in states with high levels of marginalization.